2014
DOI: 10.1097/aln.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Detection of Gastric Insufflation Related to Facemask Pressure–controlled Ventilation Using Ultrasonography of the Antrum and Epigastric Auscultation in Nonparalyzed Patients

Abstract: Inspiratory pressure of 15 cm H2O allowed for reduced occurrence of gastric insufflation with proper lung ventilation during induction of anesthesia with remifentanil and propofol in nonparalyzed and nonobese patients. (Anesthesiology 2014; 120:326-34).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 36 publications
6
123
3
3
Order By: Relevance
“…1). [18][19][20] Next, a high-frequency linear probe was applied to obtain images from the same point as that in the sagittal scanning plane. The image acquisitions were repeated five times between the peristaltic antral contractions to accurately measure the outcome variables.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). [18][19][20] Next, a high-frequency linear probe was applied to obtain images from the same point as that in the sagittal scanning plane. The image acquisitions were repeated five times between the peristaltic antral contractions to accurately measure the outcome variables.…”
Section: Methodsmentioning
confidence: 99%
“…The air in the gastric antrum was defined as the appearance of an acoustic shadow, comet-tail artefact or ringdown artefact on US. 18,22 When the signs of GI appeared, the image was saved (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is no longer the case, and research has shown that facemask ventilation using inflation pressures of less than 15cmH 2 O provides adequate ventilation without significant gastric insufflation, in the majority of non-obese individuals. 30 Two systematic reviews have since been conducted on CP, both of which showed no evidence for or against its use. 5,6 Moreover, a number of case reports, 31 surveys, 32 confidential enquiries 33 and national audits 13 have all shown that aspiration still occurs when CP is performed, with at least 11e14% of anaesthetists having witnessed aspiration during its application.…”
Section: Does Cp Prevent Gastric Regurgitation and Aspiration?mentioning
confidence: 99%
“…Although newer evidence suggests that 15 cm H 2 O may cause less gastric insufflation, it might not be high enough to produce effective mask ventilation when difficult mask ventilation is encountered. 14,15 Facial hair and edentulism are 2 commonly encountered causes of inadequate seal. Facial hair can be shaved, although it is often undesired by patients and may not be feasible in emergency situations.…”
Section: Inadequate Seal At the Mask-patient Interfacementioning
confidence: 99%